2018
DOI: 10.12681/jhvms.16063
|View full text |Cite
|
Sign up to set email alerts
|

Feedlot conditions and their influence on blood parameter values in Merino lambs in Extremadura, Spain over a specific time-period

Abstract: ABSTRACT. It has been suggested that the evaluation of specific blood parameters can be used as indicators of animal health and welfare. The aim of this study was to determine possible differences in these parameters at the beginning and at the end of the feedlot period and to analyse the influence of feedlot conditions on these animals. Blood parameter ranges can vary widely depending on factors such as transport, handling and feedlot. Four hundred and ten fattening lambs were studied to establish average val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Stress induced during handling, loading and unloading could be the cause of an enhancement of free radical production, which could cause erythrocyte lysis [ 14 ]. Our results contrast with other reports describing lower values of RBC and hematocrit at the end of the fattening than at the beginning [ 9 , 10 ]. However, in these studies, initial samples were collected after the classification and regrouping of the animals, and possible dehydration during long journeys and the first hours in the feedlot could explain these results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Stress induced during handling, loading and unloading could be the cause of an enhancement of free radical production, which could cause erythrocyte lysis [ 14 ]. Our results contrast with other reports describing lower values of RBC and hematocrit at the end of the fattening than at the beginning [ 9 , 10 ]. However, in these studies, initial samples were collected after the classification and regrouping of the animals, and possible dehydration during long journeys and the first hours in the feedlot could explain these results.…”
Section: Discussioncontrasting
confidence: 99%
“…Diet based on concentrate, ad libitum provided during the whole fattening period, could explain the significant increase in TP observed in both groups at T3 in relation to T2. Other authors also reported significant increases in TP at the end of the feedlot period, which they attributed to protein supplementation due to increasing requirements for growing lambs [ 10 ]. However, TP concentration at T3 was significantly higher in group F than in group C, despite both groups receiving the same type of concentrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the welfare state of animals at the time of arrival at the slaughterhouse will be the cumulative effects of several steps associated with handling, penning, loading and transport to the slaughterhouse (Terlouw et al., 2008 ; Ekiz et al., 2012 ; Fernandez et al., 2018 ).…”
Section: Assessmentmentioning
confidence: 99%